2022
DOI: 10.3390/ijms23052891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antiarrhythmic Drugs on Antiepileptic Drug Action—A Critical Review of Experimental Findings

Abstract: Severe cardiac arrhythmias developing in the course of seizures increase the risk of SUDEP (sudden unexpected death in epilepsy). Hence, epilepsy patients with pre-existing arrhythmias should receive appropriate pharmacotherapy. Concomitant treatment with antiarrhythmic and antiseizure medications creates, however, the possibility of drug–drug interactions. This is due, among other reasons, to a similar mechanism of action. Both groups of drugs inhibit the conduction of electrical impulses in excitable tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…In our previous work, we thoroughly studied the interactions between antiepileptic and antiarrhythmic drugs of all classes in the maximal electroshock test in mice, the commonly accepted animal model for studying tonic-clonic convulsions [ 14 ]. The involvement of oxidative stress in both cardiovascular disorders and epilepsy [ 15 ] might explain the frequent coexistence of the two diseases. For this reason, the common treatment with TMZ and antiseizure medications is very likely.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we thoroughly studied the interactions between antiepileptic and antiarrhythmic drugs of all classes in the maximal electroshock test in mice, the commonly accepted animal model for studying tonic-clonic convulsions [ 14 ]. The involvement of oxidative stress in both cardiovascular disorders and epilepsy [ 15 ] might explain the frequent coexistence of the two diseases. For this reason, the common treatment with TMZ and antiseizure medications is very likely.…”
Section: Introductionmentioning
confidence: 99%
“…The use of non-antiepileptic medicines as adjuvant agents, which have anticonvulsant properties and enhance the effects of classical AEDs, is gaining more comprehensive application. Such medicines include, in particular, non-steroidal anti-inflammatory medicines, sodium channel blockers (in particular, lidocaine), slow calcium channel blockers, β-blockers, the If-channel blocker ivabradine, the competitive xanthine oxidase inhibitor allopurinol, statins, selective phosphodiesterase-5 inhibitors (sildenafil, tadalafil), the cardiac glycoside digoxin [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to solve this problem is to use non-antiepileptic drugsmedicines, that are not classical antiepi leptic drugs (AEDs), but belong to other pharmacological groups and can be used as adjuvants. It was found that the vast majority of antiarrhythmic drugs such as sodium channel blockers (lidocaine), as well as calcium channel blockers (nifedipine, amlodipine, cinnarizine, diltiazem, verapamil) and β-blockers (propranolol, metoprolol, pindolol) have an anticonvulsant effect, which was revealed in several models of seizures in animals, and for individual drugs -in the clinic [5][6][7]. Anticonvulsant properties are also inherent in ivabradine as a blocker of I f -channels of the sinus node, used in the treatment of angina pectoris [8].…”
mentioning
confidence: 99%